Remote Delivery of Motor Function Assessment and Training for Clinical Trials in Neuromuscular Disease: A Response to the COVID-19 Global Pandemic - James, Meredith K.; Rose, Kristy; Alfano, Lindsay N.; Reash, Natalie F.; Eagle, Michelle; Lowes, Linda P. (Frontiers in Genetics, 2021)
Clinical outcome assessments of function or strength, assessed by physical therapists, are commonly used as primary endpoints in clinical trials, natural history studies and within clinics for individuals with neuromuscular disorders. These evaluations not only inform the efficacy of investigational agents in clinical trials, but also importantly track disease trajectory to prospectively advise need for equipment, home and work modifications, and other assistive devices. The COVID-19 pandemic had a global impact on the safety and feasibility of in-person visits and assessments, necessitating rapid development of mitigation strategies to ensure ongoing collection of key clinical trial endpoints and access to expert clinical care despite travel restrictions. Physical therapists who are expert in neuromuscular disorders working across clinics, countries, and clinical trials developed initial guidelines and methods for the suitability and feasibility of performing remote evaluations. A number of Sponsors introduced amendments to their study protocols to enable remote evaluations, supported by live video streaming of the assessment to their local clinical evaluators. Similarly, application of these techniques to clinical telemedicine enabled objective evaluations for use in payer discussions, equipment procurement, and general access to expert physical therapy services. Here we report on our methodology for adapting current practices to remote testing and considerations for remote evaluations.